Optimization of a Two-Warehouse Inventory Model for Deteriorating Items under Inflation and Partial Backlogging Using Genetic Algorithm - Chauhan, Neha; Yadav, Ajay Singh; Swami, Anupam (Journal of Neonatal Surgery, 2025)
This paper presents a two-warehouse inventory model for deteriorating items under stock-dependent demand, time-dependent holding cost, shortages, and inflation. Each cycle begins with shortages and ends without them, reflecting real-world supply chain dynamics. The model considers limited capacity in an owned warehouse (OW) and higher costs in a rented warehouse (RW). A Genetic Algorithm (GA) is applied to optimize key decision variables such as order quantity and cycle time, minimizing the total cost, including holding, deterioration, shortage, and transfer costs under inflation. Comparative analysis shows that the GA-based model outperforms the traditional model when inflation is present, while both perform equally in its absence. Numerical examples and sensitivity analysis validate the effectiveness and efficiency of the proposed approach.